Exploring non-mandatory travel behavior in Jakarta City: Travel time, trip frequency, and socio-demographic influences - Francisco Benita (Transportation Research Interdisciplinary Perspectives, 2023)
This study investigates non-mandatory trips in three regions of Jakarta city, namely Central, North, and West. Specifically, the focus is on examining mode choice, distance traveled, and trip frequency. The dataset used for analysis consists of 1,187 complete survey responses obtained from an on-site survey of residents conducted between December 2019 and March 2020. The results reveal distinct travel patterns across the surveyed areas. For instance, Central Jakarta exhibits a high reliance on ride-hailing services, while shorter-distance trips are more common in West Jakarta. These variations can potentially be attributed to socio-demographic factors. To gain deeper insights into travel behavior, a multinomial transport mode choice model is employed to explore the relationship between travel modes, trip characteristics, and personal/household variables. Interestingly, despite the growth of motorcycles in Jakarta, our findings suggest that older individuals are more inclined to choose walking over motorcycle travel. Additionally, trip frequency plays a role in mode choice, as frequent trips are associated with motorcycle-based travel. As anticipated, motorcycle modal share is influenced by vehicle ownership; however, our results indicate a negative impact of ownership on the likelihood of switching from motorcycle mode to alternative modes. To facilitate a shift from motorcycle use to active and public transportation, our findings emphasize the need for an effective transportation strategy that includes reducing motor vehicle ownership, creating walkable environments, and developing age-friendly public transport options.